5 Reasons To Care About Mobile Cloud Computing (Journal of Open Law, Technology & Society, 2010)
Funambol Inc.'s Fabrizio Capobianco explores the technical and market opportunities presented by the intersection of cloud technologies and rapid advances in mobile computing for Free & Open Source software. In doing so he exposes the unique needs of this new market segment, and the legal challenges which may arise from its development.